PERBAIKAN KESUBURAN TANAH LIAT DAN PASIR DENGAN PENAMBAHAN KOMPOS LIMBAH SAGU UNTUK PERTUMBUHAN DAN PRODUKTIVITAS TANAMAN PAKCOY (Brassica rapa var.chinensis) - Prasasti, Diwyacitta; Prihastanti, Erma; Izzati, Munifatul (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
This study aims to determine the growth and productivity of plants pakcoy (Brassica rapa var. chinensis) on clay or sand media after repair with the addition of starch waste compost. The research was conducted for 3 months using completely randomized design (CRD) factorial. The first factor is the type of soil, consisting of T1 (clay) and T2 (sand soil). The second factor is the concentration of compost, consisting of K0 (without compost or control), K1 (NPK), K2 (sago waste compost 25%), K3 (sago waste compost 50%), K4 (sago waste compost 75%). The results shows that the addition of compost treatment significantly effect fisikokimiawi soil conditions include soil porosity, soil pH and soil NPK content. The addition of compost effect on plant growth pakcoy include the number of leaves, plant height, root length, fresh weight and dry weight of plants. As for the type of soil showed significantly effect on soil porosity and soil NPK content. The best type of compost obtained by the addition of compost waste starch concentration of 75% and the addition of NPK fertilizer. Based on this it can be concluded that the addition of sago waste compost can improve soil media in both clay and sandy soil with nearly the same potential with the addition of NPK fertilizer.